Major Histocompatibility Complex Class II Deficiency Beyond Infancy - Aziza Bachir Kattra; Ibtihal Benhsaien; Asmaa Drissi Bourhanbour; Zahra Aadam; Abderrahmane Errami; Fatima Ailal; Ahmed Aziz Bousfiha; Jalila El Bakkouri (Case Reports in Immunology)
Major histocompatibility complex class (MHC)-II deficiency is a rare autosomal recessive combined immunodeficiency, accounting for 4.1% of inborn errors of immunity (IEI) cases in North Africa and the Middle East. Most patients do not survive beyond the age of 10 years. The cases described in this study are rare and unusual for MHC-II deficiency. We report the cases of four unrelated patients of Moroccan origin with MHC-II deficiency. Immunophenotyping of lymphocyte subpopulations and analysis of human leukocyte antigen-DR (HLA-DR) expression were performed using flow cytometry. Genetic analysis was conducted through direct sequencing. The mean age of our patients was 18.75 years (range 16–26 years); the mean age at diagnosis was 14.07 years, and the mean age of onset of symptoms was 5.25 months. The clinical presentation is characterized by recurrent pulmonary infections with predominant bronchial dilatation and hemorrhagic rectocolitis. The diagnosis was confirmed in all patients by absence of HLA-DR expression and detection of the c.338-25_338del mutation in RFXANK. Three (75%) of our patients are still alive and are on monthly intravenous immunoglobulin (IVIG) therapy. It is important to consider MHC-II deficiency in the differential diagnosis of combined immunodeficiencies across all age groups. Further studies are needed to elucidate the various phenotypes associated with this condition.